Purification and characterization of a lectin from endophytic fungus fusarium solani having complex sugar specificity - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Archives of Biochemistry and Biophysics, 2007)
A lectin from the mycelial extract of an endophytic strain of Fusarium solani was purified. Its hemagglutinating activity was inhibited by glycoproteins possessing N-linked as well as O-linked glycans. The thermodynamics and kinetics of binding of glycans and glycoproteins to F. solani lectin Was Studied using SUH ace plasmon resonance. The lectin showed high affinity for asialofetuin, asia-lofibrinogen, asialofibrinogen, and thyroglobulin: and comparatively low affinity for mucin, fetuin, fibrinogen, and holotransferrin. Glycoproteins showed glycans with significant contribution from enthalpy and positive entropy, suggesting several fold higher affinity than their corresponding g the involvement of non-polar protein-protein interaction. Moreover, the higher affinity of the glycoproteins was due to their faster association rates and low activation energy. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: endophytic fungus; Fusarium solani; Lectin; Purification; SPR; Thermodynamic properties